Democratic demand and supply: a spatial model approach to satisfaction with democracy. Issue 3 (3rd July 2019) - Heyne, Lea
ABSTRACT: Satisfaction with democracy (SWD) is a commonly used indicator, and its determinants have been analysed extensively. But what does dissatisfaction with democracy substantially mean? This paper tests if satisfaction is actually a coherent consequence of citizens considering democratic supply and demand. It starts from the simple idea that satisfaction can be explained by the distance between what "should be" and what "is"; between democratic expectations and reality. I capture this idea in a spatial model of democratic support, where size and direction of the gap between citizens' expectations and evaluations of democracy determine levels of satisfaction. I use data for 26 countries from the European Social Survey. Taking into account both expectation-surplus and evaluations-surplus gaps, I find that satisfaction is affected by both the size and the direction of the distance between expectations and evaluations. The main finding is that liberal criteria of democratic quality are generally agreed upon amongst citizens, and that a perceived lack of their realization is the strongest predictor of dissatisfaction. Democratic input dimensions like direct participation and output criteria like social justice are more disputed, and create dissatisfaction amongst those wanting more of them as well as those wanting less.